Pengaruh Motivasi Belajar Dan Fasilitas Belajar Terhadap Prestasi Belajar Bahasa Arab Siswa Di SD Alam Ar-Rohmah Malang - Kurniawan, Wahyu; Anwar, Najih (Universitas Hamzanwadi, 2025)
This research aims to investigate and analyze the influence of learning motivation and learning facilities on the Arabic language learning achievement of students at SD Alam Ar-Rohmah Malang, using a quantitative approach with an associative research type. The study involved 32 students from class VB, employing a total sampling or census technique, which included the entire population. The research variables consisted of independent variables, namely learning motivation (X1) and learning facilities (X2), and a dependent variable, namely Arabic language learning achievement. Data analysis was conducted using multiple regression to predict fluctuations in the dependent variable. The results indicated that both learning motivation and learning facilities have a significant influence on students' Arabic language learning achievement, where an increase in motivation and quality of learning facilities correlates with an increase in learning achievement.